Body Mass Index, Physical Activity, and Body Image in Adolescents - Marja H. Leppänen; Aku-Ville Lehtimäki; Eva Roos; Heli Viljakainen (MDPI AG, 2022)
Body image dissatisfaction is a concern for adolescents' mental and physical well-being, and the role of body mass index (BMI) and physical activity (PA) in it is still unclear. This study investigates the associations of BMI and PA with body image, separately for boys and girls, in a large sample of Finnish adolescents. We also examine the associations of BMI with body image in varying PA levels. A total of 10,496 adolescents (girls 52.6%) were included in the analyses. Body image was assessed using a pictorial tool, and categorized as wishing for a smaller body, being satisfied, and wishing for a bigger body. BMI (kg/m2) was categorized as thin, normal weight, and overweight/obese. Self-reported PA was divided into three similar-sized categories as low, moderate, and high PA levels. Adjusted ordinal regression analyses were conducted. Our results show that adolescents with thinness had higher odds of wishing for a bigger body compared to their normal-weight peers, while adolescents with overweight/obesity had smaller odds of wishing for a bigger body. Adolescents in low and middle PA levels had lower odds of wishing for a bigger body compared to adolescents in the high PA level. Yet, the PA level modified the associations between BMI and body image, especially in adolescents with thinness and more so in girls than in boys. These findings highlight the need to pay attention to healthy weight gain and PA in adolescents to support their body image satisfaction.